Assessing the content specificity of interpretation biases in community adolescents with persistent and interfering pain. Issue 2 (February 2020) - Lau, Jennifer Y.F.; Badaoui, Maryam; Meehan, Alan J.; Heathcote, Lauren C.; Barker, Edward D.; Rimes, Katharine A.
Abstract : Abstract: The tendency to select threatening over benign interpretations of ambiguous bodily sensations and cues characterises young people with chronic pain. However, previous studies disagree over whether these biases extend to nonbodily harm situations such as social evaluation. Understanding the content of these biases is crucial to the development of pain management strategies seeking to modify such biases. Two hundred forty-three young people aged 16 to 19 years completed an expanded version of the Adolescent Interpretation of Bodily Threat task. Using a factor-analytic approach, we removed items that did not consistently associate with bodily harm or social evaluation. Next, we examined whether the variance underlying negative and benign interpretations of bodily harm and social evaluation situations were best represented as a common factor (ie, one-factor model), 2 distinct factors (ie, 2-factor model), or one common and 2 distinct factors (ie, 2-factor bifactor model) in all adolescents. We then compared youth with and without persistent and impairing pain on factor scores derived from the best-fitting model. Although negative interpretations of bodily harm and social evaluation situations emerged as distinct factors, benign interpretations across situations were best captured by a common factor and 2 situation-specific factors (ie, bifactor model). Group comparisons showed that young people with moderate-to-high pain interference were more likely to endorse negative interpretations across all situations, and less likely to manifest a general benign interpretational style, than youth without interfering pain, although some of these group differences were explained by co-occurring anxiety and depressive symptoms. Replication of these findings is needed. Abstract : Supplemental Digital Content is Available in the Text.Young people from the community with persistent and interfering pain interpret all situations, not just bodily harm, more negatively and less positively.